Determinats of irritant contact dermatitis in seaweed farmers - Rahmansyah, Sitti Fatimah; Salcha, M. Akbar; Juliani, Arni; Abuda, Hisbullah A.M (CORE JOURNAL, 2022)
Irritant contact dermatitis is an acute or chronic skin inflammatory response to exposure to external irritants that affect the skin. One type of work that is easily exposed to irritants is seaweed farming, because of the hydroid content in seaweed. The purpose of this study was to determine the factors associated with the symptoms of irritant contact dermatitis in seaweed farmers in Dusun Lomboan, distric. South Tinangkung Regency Banggai Kepulauan. This study uses a type of analytical observational research with a cross sectional study approach. The sample in this study were 40 workers using the total sampling technique. Data collection was carried out through observation, interviews and questionnaires. Data were analyzed using the Chi-Square test. The statistical test results showed that contact duration (p value = 0.012), years of service (p value = 0.001), personal hygiene (p value = 0.013) and history of skin disease (p-value = 0.015) had a relationship with irritant contact dermatitis symptoms. It is recommended for seaweed farmers to use PPE when working, for example rubber gloves, special shoes, to avoid direct exposure which can cause irritant contact dermatitis. Also always maintain personal hygiene after doing work such as washing hands using soap with running water and bathing to avoid the risk of irritant contact dermatitis